2021
DOI: 10.1021/acs.est.0c07670
|View full text |Cite
|
Sign up to set email alerts
|

In Situ DGT Sensing of Bioavailable Metal Fluxes to Improve Toxicity Predictions for Sediments

Abstract: An increased risk of adverse biological effects of metals in sediments may be accompanied by high labile metal fluxes as measured by the diffusive gradients in thin films (DGT) technique. To improve the usefulness of the DGT technique for sediment quality risk assessments, we used the simpler and more cost-effective piston DGTs rather than planar DGT probes to measure bioavailable metal fluxes in naturally contaminated sediments with widely varying composition (properties, metals and concentrations) and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…IHg content was determined by the difference between TotHg and MeHg contents in the sample. Metal uptake flux into DGT samplers is influenced by the soluble metal concentration and diffusion rate as well as resupply of soluble metal in the water through desorption/dissolution reactions during the DGT deployment period. ,, Thus, we interpret this flux value to represent the amount of chemically labile Hg (originating from both aqueous and particulate forms) at the DGT sampling surface.…”
Section: Methodsmentioning
confidence: 99%
“…IHg content was determined by the difference between TotHg and MeHg contents in the sample. Metal uptake flux into DGT samplers is influenced by the soluble metal concentration and diffusion rate as well as resupply of soluble metal in the water through desorption/dissolution reactions during the DGT deployment period. ,, Thus, we interpret this flux value to represent the amount of chemically labile Hg (originating from both aqueous and particulate forms) at the DGT sampling surface.…”
Section: Methodsmentioning
confidence: 99%
“…DGT is an in situ method that measures metal chemical speciation developed for water, soil, and sediment (Zhang and Davison 2015 ). The technique has been applied to monitor labile metal concentrations and, thus, to provide an estimate of metal bioavailability in natural freshwaters (Meylan et al 2004 ; Sigg et al 2006 ; Uher et al 2018 ), contaminated soils (Manzano et al 2019 ; Xu et al 2019), sediments (Xie et al 2021 ), and in three studies of stormwater runoff (Dunn et al 2007 ; Hayman et al 2019 ; McDonald et al 2022 ). Another analysis considered to provide a better indication of potential bioavailability (compared to total metal concentrations), is the analysis of the pore water of contaminated sediments (Hin et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…If the conditions of the DGT deployment are met e.g., linear concentration gradient can be formed through the gel between the high and low concentrations of the device, the DGT devices could be deployed vertically, as shown in a recent study were the DGT pistons were buried in a way that the upper edge of the DGT pistons were level with the sediment surface. 34 The successful applications of the DGT technique for determining the concentrations of ZnO NPs in this research reflects the potential of DGT as an in situ and reliable tool for evaluating the available concentrations of different types of engineering nanomaterials in soils. DGT devices with different MWCO dialysis membranes can be used for identifying dissolution kinetics of metal-based NPs in soils which is crucial for understanding their ecotoxicological impacts in the environment.…”
Section: Dgt Measurementsmentioning
confidence: 72%
“…Previous studies have shown promising results for the application of DGT devices to measure metal bioavailability and assess toxicity risk in soils and sediments both in lab and in situ, which indicate the potential for deploying modified DGT devices (with DM) in field tests. 33,34 In this study, as shown in Figure 1 and 2, the DGT devices were pushed about 3 mm below the soil surface to have good contact with the soil samples. If the conditions of the DGT deployment are met e.g., linear concentration gradient can be formed through the gel between the high and low concentrations of the device, the DGT devices could be deployed vertically, as shown in a recent study were the DGT pistons were buried in a way that the upper edge of the DGT pistons were level with the sediment surface.…”
Section: Dgt Measurementsmentioning
confidence: 85%